Pupil Dilation with Intracameral Epinephrine Hydrochloride during Phacoemulsification and Intraocular Lens Implantation. (20th January 2016) - Yu, A-Yong; Guo, Hua; Wang, Qin-Mei; Bao, Fang-Jun; Huang, Jing-Hai
Abstract : Objective . To investigate mydriatic effect of intracamerally injected epinephrine hydrochloride during phacoemulsification and intraocular lens (IOL) implantation. Methods . Eighteen cataract patients for bilateral phacoemulsification were enrolled. To dilate pupil, one eye was randomly selected to receive intracamerally 1 mL epinephrine hydrochloride 0.001% for 1 minute after corneal incision (intracameral group), and the contralateral eye received 3 drops of compound tropicamide 0.5% and phenylephrine 0.5% at 5-minute intervals 30 minutes before surgery (topical group). Pupil diameters were measured before corneal incision, before ophthalmic viscoelastic device (OVD) injection, after OVD injection, before IOL implantation, and at the end of surgery. Results . At each time point, the mean pupil diameter in the intracameral group was2.20 ± 0.08, 5.09 ± 0.20, 6.76 ± 0.19, 6.48 ± 0.18, and5.97 ± 0.24  mm, respectively, and in the topical group it was7.98 ± 0.15, 7.98 ± 0.15, 8.53 ± 0.14, 8.27 ± 0.16, and7.93 ± 0.20  mm, respectively. The topical group consistently had larger mydriatic effects than the intracameral group (P < 0.05 ). The onset of mydriatic effect was rapid in the intracameral group. There was no difference in surgical performance or other parameters between groups. Conclusions . Intracameral epinephrine hydrochloride appears to be an alternative to the mydriatic modalities for phacoemulsification and IOL implantation. In comparison with topical mydriatics, intracameral epinephrine hydrochloride offers easier preoperative preparation, more rapid pupil dilation, and comparable surgical performance.